Magnetic characteristics of Guangshan loess from northern piedmont of Dabie Mountains, east-central China. Issue 2 (7th May 2020) - Han, Yan; Liu, Xiuming; Zhao, Guoyong; Zhang, Zhenke; Lü, Bin; Chen, Qu
SUMMARY: The loess from the northern piedmont of the Dabie Mountains is in a transition area between loess from the Chinese Loess Plateau, the Quaternary red soils of southern China and the Xiashu loess. Despite its significant location, the study has been inadequate. In this study, the Guangshan section in the northern piedmont of the Dabie Mountains was selected for investigation. Environmental magnetism, geochemistry, colour reflectance and optical diffuse reflection spectroscopy analyses were applied to detect the magnetic variations in the loess. The results showed that (1) the magnetic minerals consisted mainly of magnetite, maghemite, hematite and goethite, which are the same as those in the Quaternary loess from the Chinese Loess Plateau, the Xiashu loess and the Quaternary red soils of southern China. The average magnetic particles were in the pseudo-single domain, like those of the Chinese Loess Plateau loess. (2) Unit III of the Guangshan section (2.4–4 m), with high chemical index of alteration and low Ba-index, was demonstrated as the most strongly developed palaeosol in the whole section, in agreement with field observations (more Fe-Mn films and weakly vermiculated development). However, it exhibited minimal susceptibility values and the lowest concentration of fine ferrimagnetic minerals. Simultaneously, the unit had low hematite to goethite ratio (Hm/Gt), suggesting that the pedogenic environment was humid; and it also had high values of b * and Gt%, implying that there was more goethite. Therefore, we can conclude that excessive soil moisture and intensive pedogenesis dissolved the fine ferrimagnetic minerals originally produced by pedogenesis and transformed them into goethite. These results could help to trace the palaeoclimatic evolution of the study area and clarify the magnetic variations of loess in different climates throughout China.